RNA-based blood genomics as an investigative tool and prospective biomarker for ischemic stroke. (1st June 2013) - Cox, Christopher; Sharp, Frank R
Abstract : Stroke is a leading cause of death and disability, and considerable effort is being expended to investigation of its pathological mechanisms, as well as the identification of clinically relevant biomarkers that could assist in diagnosis. RNA-based analysis of gene expression in blood represents a new field of study addressing both paradigms. A number of recent animal and human studies using microarray technology demonstrate rapidly-induced, measurable changes in gene expression in response to ischemic trauma, and distinct expression 'profiles' specific to the injury subtype. The incorporation of newer technologies for a more detailed transcriptome analysis holds great promise for further improving our knowledge of stroke at the molecular level, and potentially enhancing standards of diagnosis.